2011
DOI: 10.1103/physrevb.84.020503
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-beam epitaxy and robust superconductivity of stoichiometric FeSe crystalline films on bilayer graphene

Abstract: We report on molecular beam epitaxy growth of stoichiometric and superconducting FeSe crystalline thin films on double-layer graphene. Layer-by-layer growth of high-quality films has been achieved in a well-controlled manner by using Se-rich condition, which allow us to investigate the thickness-dependent superconductivity of FeSe. In situ low-temperature scanning tunneling spectra reveal that the local superconducting gap in the quasiparticle density of states is visible down to two triple layers for the mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
128
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 23 publications
13
128
1
7
Order By: Relevance
“…Type A defects appear as two bright spots on neighboring atom sites and have been previously identified as a Se atom on or close to an Fe site [20][21][22] or an Fe vacancy [23]. Type B defects appear as depressions at an atomic site at the top of the film.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Type A defects appear as two bright spots on neighboring atom sites and have been previously identified as a Se atom on or close to an Fe site [20][21][22] or an Fe vacancy [23]. Type B defects appear as depressions at an atomic site at the top of the film.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…• C, again for 12 h. There is very limited mention of superconducting films grown by other common techniques, such as molecular beam epitaxy [27,28], metalorganic chemical vapor deposition (MOCVD) [29] and sputtering [30]. Recently, very thick (thickness 100 µm) superconducting films of FeSe (T onset c = 8 K) were successfully deposited by electrochemical route [31].…”
Section: Synthesis Morphology and Crystalline Structurementioning
confidence: 99%
“…Films grew epitaxially as confirmed by XRD patterns, and φ scan demonstrates that in-plane (100) and (010) axes of the FeSe thin film were aligned parallel to the (1-10) and (001) axes of the YAlO 3 substrate (figure 11). Song et al [46] reported on MBE of stoichiometric and superconducting FeSe crystalline thin films on double-layer graphene that was formed on SiC(0001). It was shown by scanning tunneling microscopy (STM) that this new kind of substrate can yield strain-free FeSe films.…”
Section: Fese X Filmsmentioning
confidence: 99%
“…Attempts at merging of graphene with FeSe were made previously. Thus, the floating phenomenon in case of FeSe on graphene [28] is taken as starting point in the present investigation.…”
Section: Resultsmentioning
confidence: 99%